Estudo de caso sobre o "cabo de guerra" argumentativo na judicialização da reprodução assistida - Heidemann, Samuelli Cristine Fernandes (2023)
This thesis aims to analyze the phenomenon of judicialization of assisted reproduction, by evaluating and interpreting the rhetorical arguments that make up the legal divergence about the conception of a baby through technological procedures, when legal claims are imputed to the Public Power, as a rule, via the Unified Health System (SUS) and, exceptionally, via private means, bear the onerous costs of using reproductive techniques. The main theses raised in the demands include, on the one hand, that: assisted reproduction is not included in the fundamental right to health, as it aims at the conception of a child, so that the absence of pregnancy does not correspond to the absence of health; yet, not uncommon is the argument of reserving the possible, which highlights the permanent budgetary difficulty of the State, alerting, above all, to the state inequality in benefiting a few to the detriment of the whole community. On the other hand, the World Health Organization (WHO) embraces a broad concept of disease, in which infertility is inserted; Likewise, the Federal Constitution of 1988 accepted the right to health in an extensive category – provision, promotion and prevention – comprising assisted reproduction. Family planning is another recurring claim when it is linked to reproductive and health rights, it concerns reproductive freedom materialized in the individual decision on the use of contraceptive and contraceptive methods, that is, whether or not to have children, how many children and at what interval of time. This confrontation of arguments, added to the lack of specific legislation on assisted reproduction, legitimize its judicialization and provide different positions of the magistrates that, consequently, result in different decisions. Therefore, the legal controversy established legitimizes and motivates us to evaluate this argumentative “tug of war”. Therefore, we will use the case study as a research strategy, through a descriptive/exploratory analysis. The empirical investigation comprises a single case, the Civil Appeal 5005258-03.2014.4.04.7004/PR, judged by the Third Panel of the Federal Regional Court of the 4th Region, elected for characterizing the ideal portrait of legal divergence.